Development of the method for assessing the action zones of hazards in an emergency at a city filling station using geoinformation technology - Vasiutynska, Kateryna; Arsirii, Olena; Ivanov, Oleksii (Technology audit and production reserves, 2017)
The object of research is a specific filling station (gas station), which is located in the Odessa (Ukraine) on the Gastello street. Filling station recepts and stores petroleum products (gasoline A-80, A-93, diesel fuel, engine oil) and refueling vehicles. The facility includes a tank of 40 m3 of tank fuel and 1 tank of 15 m3 tanks. The area of influence includes a motorway, a garage cooperative, a cafe-bar, a multi-storey house, a gas distribution station. One of the most problematic places of operation of the filling station is emergency risk – fire and explosion, as a result of leakage and the accumulation of fumes of oil products. Therefore, local destruction of the reservoir is considered with subsequent ignition of the leak, which led to the appearance of a shock wave. In the course of the research, a method for assessing the zones of action of damaging factors is developed, in which geographical information technologies are used. The method includes the steps of selecting an emergency scenario, processing the primary data, calculating the values and radii of the zones of the component parameters of the emergency situation. Visualization of the destruction zones in Quantum GIS version 2.18.2, with an open information code, distributed under the terms of the GNU General Public License is also included. Based on calculations of the size of hazardous areas in which full, medium, weak destruction of buildings and related injuries in humans are possible, the results of their visualization based on the architecture of an integrated geographic information system (GIS) are possible. The proposed method has a number of features, in particular, it allows to identify a specific city territory, which is covered by negative factors of accident consequences, in on-line mode. Due to this, certain «care» objects that have fallen into the corresponding risk zones, among which are 2 multi-storey houses, a gas distribution station, a cafe-bar, a garage cooperative, a significant part of the motorway. In comparison with similar known examples of risk analysis, the method allows to classify the «care» objects by the levels of damage, and organize appropriate measures to minimize risks in the environmental management system of the city. The method provides such advantages as systemic representation of potentially dangerous objects and subjects of their influence, the integration of branched development scenarios, visibility, cross-platform and openness of information data. Using the method of modeling the development of an emergency at filling stations within the city of a million people improves the efficiency of the information presentation, allows to adequately predict the development of the environmental situation in the risk management system. And also positively affects the work of the SES bodies in ensuring the technogenic security of the city.